Z historii polskiej surdopedagogiki – trudne początki - Szczepankowski , Bogdan (Studia Edukacyjne, 2017)
The Institute for the Deaf-mute in Warsaw, established in 1817 by Father Jakub Falkowski, is commonly considered to be the firstschool for deaf-mute children in Poland. However, similar actions had been taken three times earlier: in 1803 in Romanow, Volhynia, in 1804 in Vilnius, and in 1809 in Warsaw. Unfortunately, those activities did not generate the expected effects. The article recalls those unsuccessful attempts of establishing the first schools for deaf children